UMRAH WORSHIP SERVICE STRATEGY IN AN EFFORT TO INCREASE CONGREGATION SATISFACTION - Naylal Fithri; Andriyana Andriyana (JURNAL PROFIT, 2025)
Indonesia has the largest Muslim population in the world, making interest in carrying out Umrah very high, especially due to the limited Hajj quota. This study aims to analyze the influence of service quality on the satisfaction and loyalty of Umrah pilgrims at PT Qiblatain Sakti, Gending, Probolinggo. The descriptive qualitative method was used with data from observations and interviews with 5 pilgrims and 2 officers. The results found that service aspects such as responsiveness, assurance, reliability, tangible, and empathy had a significant impact on congregation satisfaction and loyalty. Good service quality can increase the satisfaction and loyalty of Umrah pilgrims. This study recommends improving service strategies to increase congregational trust.